New Insights into the Metabolism of the Flavanones Eriocitrin and Hesperidin: A Comparative Human Pharmacokinetic Study - María Ángeles Ávila-Gálvez; Juan Antonio Giménez-Bastida; Antonio González-Sarrías; Juan Carlos Espín (MDPI AG, 2021)
The intake of hesperidin-rich sources, mostly found in orange juice, can decrease cardiometabolic risk, potentially linked to the gut microbial phase-II hesperetin derivatives. However, the low hesperidin solubility hampers its bioavailability and microbial metabolism, yielding a high inter-individual variability (high vs. low-producers) that prevents consistent health-related evidence. Contrarily, the human metabolism of (lemon) eriocitrin is hardly known. We hypothesize that the higher solubility of (lemon) eriocitrin vs. (orange) hesperidin might yield more bioavailable metabolites than hesperidin. A randomized-crossover human pharmacokinetic study (n = 16) compared the bioavailability and metabolism of flavanones from lemon and orange extracts and postprandial changes in oxidative, inflammatory, and metabolic markers after a high-fat-high-sugars meal. A total of 17 phase-II flavanone-derived metabolites were identified. No significant biomarker changes were observed. Plasma and urinary concentrations of all metabolites, including hesperetin metabolites, were higher after lemon extract intake. Total plasma metabolites showed significantly mean lower Tmax (6.0 ± 0.4 vs. 8.0 ± 0.5 h) and higher Cmax and AUC values after lemon extract intake. We provide new insights on hesperetin-eriodictyol interconversion and naringenin formation from hesperidin in humans. Our results suggest that regular consumption of a soluble and eco-friendly eriocitrin-rich lemon extract could provide a circulating concentration metabolites threshold to exert health benefits, even in the so-called low-producers.